Differences in Weight Loss and Recovery After Cleft Lip and Palate Repair. (February 2019) - Kaye, Alison; Che, Columbine
Objective: To determine the degree of weight loss, time to regain lost weight, and impact on postoperative outcomes after primary cleft lip (CL) and cleft palate (CP) repair. Design: Single institution retrospective. Patients: Two hundred seven patients who underwent primary CL and/or CP repair procedures. Results: One hundred thirty primary CL repairs (isolated CL = 59; cleft lip and palate [CLP] = 71) and 140 primary CP repairs (isolated CP = 72; CLP = 69): At the first postoperative visit, 21.54% of CL and 57.14% of CP repair patients had not returned to their immediate preoperative weights ( P < .0001). Maximum weight loss after CL repair was 0.44 kg (mean = 0.15 kg; standard deviation [SD]: 0.11) and for CP repair was 0.85 kg (mean = 0.31 kg; SD: 0.21; P = .002). Maximum percentage body weight loss was 6.11% after CL repair (mean = 2.08%; SD: 1.56) and 9.2% after CP repair (mean = 3.10%; SD: 2.13; P = .02). If not returned to preoperative weight by first postoperative visit, CP repair took significantly longer. Median time to return to preoperative weight was CL = 14.08 days (interquartile range [IQR]: 7.26) and CP = 25.37 days (IQR: 21.07; P < .0001). Patients undergoing CP repair with slowed weight recovery had a 22.5% rate of unintentional fistula/partial dehiscence compared to 10.0% of those who recovered quickly ( P = .052). Conclusions: Primary CP repair involves significantly higher risk and degree of postoperative weight loss and slower rates of weight recovery when compared with primary CL repair. Postoperative weight loss is associated with increased risk of complications with palatal healing. Cleft palate repair patients should be monitored closely for weight recovery and considered for nutritional interventions to support improved postoperative outcomes.